Morphometry Study on Thoracic Vertebrae Pedicle with Computed Tomography Scan in Population of Surabaya, Indonesia - Yoki Surya1, I Ketut Martiana1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The fixation technique with pedicle screw is widely used for stabilization as well as deformity correction. However, data on vertebral morphometry have not been obtained. Most previous studies were conducted on the Caucasian race and slightly in the Asian race considering that there was a significant difference in pedicle morphometry of vertebrae between races and age. The objective to examine the morphometry of the thoracic vertebral pedicle in young adult population of Surabaya, comparing with the pedicle morphometry in the overseas population. The method we collected patients’ data of thorax CT Scan in Dr. Soetomo Teaching Hospital and Airlangga Hospital Surabaya. Patients with spinal deformities including congenital abnormalities, trauma, infection, and tumors were excluded. The variables to be measured were pedicle diameter (Pedicle width), pedicle depth to anterior cortex corpus vertebrae (Cord Length), and transverse pedicle angle. The result CT scan data collected was 123 consisting of 56 males and 67 females with an average age of 18.1 years old. The average pedicle width, cord length, and transverse pedicle angle in Surabaya population differed significantly from the Caucasian population of the previous study. Conclusion there were no significant differences in transverse pedicle angle between males and females. There was no significant difference in morphometric data compared to the Asian population.